Improving student achievement with smart sheets Media in islamic cultural history lesson at the Elevent grade students of mtsn tarusan - Sasmini Sasmini (Jurnal Ilmiah Pendidikan Scholastic, 2017)
To be able to learn something well, we need to hear, see, ask questions about it, and discuss it with others. Not only that, teachers need to "do", which describe something in their own way, showing for example, tried to practice skills and tasks that require p What Knowledge they have earned. Problems to be studied in this research are: a) How improve learning outcomes Islamic cultural history through smart method in class XI sheets MTsN Tarusan in July 2016? b) The steps made in improving the learning outcomes of students of Islamic cultural history? This research is a Class Action Research (PTK), as for the steps to be performed in this PTK model developed by Kurt Lewin as mentioned in Dikdasmen (2003: 18) that the stages or so-called cycle (round) consists of four components which cover : (A) planning, (b) action / acting, (c) observation, (d) reflection. Based on The results of learning activities that have been conducted during the study, and based on all the discussion and analysis that has been done can be summed up as follows: Learning with smart method sheets in Islamic cultural history lesson positively in improving student achievement that is marked by a mastery learning students in learning, namely (97.29%). Application of the method school library media on learning history of Islam have a positive effect, which can increase students' motivation is indicated by an average of 8 0 and from interviews stating that students are interested and interested deng a n cooperative methods Learning the history of Islamic culture so that they become motivated to learn.